Intellectual property law and the fourth industrial revolution - Heath, Christopher; Kamperman Sanders, Anselm; Moerland, Anke 1983- (Alphen aan den Rijn, The Netherlands Kluwer Law International, 2020)
Intellectual Property Law and the Fourth Industrial Revolution' analyses how the fourth industrial revolution changes the framework of intellectual property rights in the context of data, competition and compliance and how these changes can serve society. It is in the very nature of intellectual property rights that their justification and scope correlate with extraneous factors, such as societal perception and technological development. The convergence of various fields of technology is changing the fabric of society. Big data and data mining, Internet of Things, artificial intelligence and blockchains are already affecting business models and leading to social and economic transformations that have been dubbed by the fourth industrial revolution.
Summary of Contents
Part 1 – The Greater Picture. Chapter 1. The Disruptive Nature of the So-Called Fourth Industrial Revolution for Intellectual Property: Moving Societal Changes from Linear to Exponential, Manuel Desantes Real--- Chapter 2. The Fourth Industrial Revolution, Development and Intellectual Property: The World Economic and Social Survey 2018 and Beyond, Hoi Wai Jackie Cheng & Mariangela Parra-Lancourt. Part 2 – Data as the New Currency of the Fourth Industrial Revolution. Chapter 3. Regulating Net Neutrality in a Data-Centric Society, Carlos Affonso Souza & Filipe Ribeiro Duarte--- Chapter 4. Balancing AI Bias, Michael Mattioli. Part 3 – The Impact of the Fourth Industrial Revolution on Intellectual Property and Competition Law. Chapter 5. Artificial Intelligence and the Protection of Literary and Artistic Works, Gonçalo Cabral--- Chapter 6. Patents and Artificial Intelligence Inventions, Kemal Bengi & Christopher Heath--- Chapter 7. New Trade Mark Uses in the Fourth Industrial Revolution: Virtual and Augmented Realities, Anke Moerland--- Chapter 8. Data and Technology Transfer: Competition Law in the Fourth Industrial Revolution, Anselm Kamperman Sanders. Part 4 – Monitoring, Compliance and Enforcement. Chapter 9. Intermediary Liability in the Fourth Industrial Revolution, Michael B. Landau--- Chapter 10. Smart Contracts, Blockchain and Intellectual Property: Challenges and Reality, Andres Guadamuz.
Includes bibliographical references and index.
Keywords: Intellectual property; Technology and law; Technological innovations -- Law and legislation; Intellectual property; Technology and law; Technological innovations -- Law and legislation